The effectiveness of psychoeducation programs following first episode psychosis: a systematic review protocol. (December 2016) - Matoba, Kei; Kajiwara, Tomomi; Endo, Yoshimi; Makimoto, Kiyoko
Abstract : Review question/objective: The objective of this review is to establish whether psychoeducational programs can lead to improved outcomes (reduced relapse or readmission) in patients with first-episode psychosis (FEP) compared with usual care. Specifically, the review question is: Are psychoeducational programs for patients with first-episode psychosis effective in improving outcomes compared with those receiving usual care?